PENGARUH IPM, DANA DESA DAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI 13 KABUPATEN/KOTA DI KALIMANTAN SELATAN - AKHMAD RIPANDI (PPJP Universitas Lambung Mangkurat, 2018)
The purpose of this research is the 13 districts/cities of the province of South Kalimantan consisting of 11 districts ( Kotabaru, Banjar, Tanah Laut, Barito Kuala, Tapin, Hulu Sungai Selatan, Hulu Sungai Utara, Hulu Sungai Tengah, Balangan, Tabalong, Tanah Bumbu) and 2 cities (Banjarbaru, Banjarmasin). This study uses the panel’s return data analysis ti the Fixed Effect Model. The results of this study show that the index of human development, village funds and infrastructure at the same time has a significant impact on economic growth. The result of this study also indicate that the human development index is the dominant factor affecting economic growth in districts/cities in South Kalimantan in 2012-2016.